Construction Waste and Its Initiatives Managing among Malaysian’s Practice (Review) - Mahdi M. Abdullah; Riduan Yunus; Ahmed Saleh Ahmed Saif AL-SHAMERI (Communications of International Proceedings, 2020)
Initiatives concern in construction industry is one of the important terms that have dealt with management of construction materials with a huge concern to the social and monetary of the nationwide with a positive generation for the wealth and development. The inadequate deal with waste management administration among the construction players and practitioners rehearses has prompted such as fruitless outcome in diminishing of ecological effects and unlawful dumping for construction waste materials either during construction and build or demolition. This paper presents such a review on the construction waste management in Malaysian construction industry with the use of initiatives management toward the development that have been actualized in the Malaysian government and construction industry practice as far as to meet the development and technology involve toward construction waste management that apparently used in the current materials management in construction  this paper fills in the gaps with effective  way  that enhance from the existing practices toward an effective construction waste management.
Keywords: Construction Waste; Initiatives for Managing Construction Waste.